Catalytic methane pyrolysis for simultaneous production of hydrogen and graphitic carbon using a ceramic sparger in a molten NiSn alloy - Kim, Jina; Oh, Changgeun; Oh, Hyunseok; Lee, Youngjae; Seo, Hyungtak; Kim, Yu Kwon (Carbon, 2023)
Catalytic methane pyrolysis (CMP) for simultaneous hydrogen and carbon production has been achieved in molten NiSn liquid alloys, with the additional benefit of spontaneous separation of solid carbon from the liquid catalyst. Here, the use of ceramic spargers for the injection of CH4 bubbles into the molten liquid has shown to be advantageous not only in enhancing the CH4 conversion above 90%, but also in producing graphitic carbon. When a quartz tube was used to feed CH4 bubbles into the molten alloy, the conversation was limited to about 15–25% and the quality of the graphitic carbon product was more defective and disordered. Regardless of the use of the spargers, carbon precipitates preferentially accumulate at the top of the molten alloy, and steady-state conversion over 24 h with high selectivity towards H2 was achieved under a constant flow rate of pure CH4 without any pressure increase. The synergistic effect of the ceramic sparger on molten NiSn may be the result of a controlled bubble size of CH4 and a catalytic role of zirconia surfaces in contact with the molten alloy. Our results imply that there is a great opportunity to improve CMP in molten alloy catalysts further toward a scalable production of H2 and graphitic carbon with a nearly complete conversion of CH4.
Keywords: Alloy catalyst; Catalytic methane pyrolyse; Ceramic sparge; CH 4; Graphitic carbons; Methane pyrolysis; Molten alloy; Molten alloy catalyst; Ni-sn alloys; Production of hydrogen; Catalytic methane pyrolysis; Ceramic sparger; Graphitic carbon; Hydrogen production; Molten alloy catalyst; NiSn alloy